Chauffeur in der Führerkabine eines Lastwagens
Verkehr;Organisation des Verkehrs (allgemein);Organisation des Verkehrs (speziell);Beförderungspersonal;Fahrpersonal Verkehr;Organisation des Verkehrs (allgemein);Organisation des Verkehrs (speziell);Verkehrsunternehmen